2009
DOI: 10.1016/j.psyneuen.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ cortisol responses to awakening and social stress; Effects of gender, menstrual phase and oral contraceptives. The TRAILS study

Abstract: . (2009). Adolescents' cortisol responses to awakening and social stress; Effects of gender, menstrual phase and oral contraceptives. The TRAILS study. Psychoneuroendocrinology, 34(6), 884-893. DOI: 10.1016884-893. DOI: 10. /j.psyneuen.2009 Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
181
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(207 citation statements)
references
References 48 publications
22
181
1
3
Order By: Relevance
“…Among the women in our study, the use of hormonal contraception did not affect the cortisol response to stress. This is in contrast to some previous work that, while reporting no effect of menstrual cycle phase on cortisol levels, found that women taking hormonal contraceptives showed a blunted cortisol stress response (Bouma et al, 2009;Liening et al, 2010). Several studies also show a greater increase in free cortisol levels among men than women in response to psychosocial stress (reviewed in Kudielka and Kirschbaum, 2005), therefore the present study warrants replication among men.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Among the women in our study, the use of hormonal contraception did not affect the cortisol response to stress. This is in contrast to some previous work that, while reporting no effect of menstrual cycle phase on cortisol levels, found that women taking hormonal contraceptives showed a blunted cortisol stress response (Bouma et al, 2009;Liening et al, 2010). Several studies also show a greater increase in free cortisol levels among men than women in response to psychosocial stress (reviewed in Kudielka and Kirschbaum, 2005), therefore the present study warrants replication among men.…”
contrasting
confidence: 99%
“…Considerable variation in people's responses to various stressors has been well documented, and has been tied to factors such as sex, smoking habits, various illnesses, steroid use, and the use of hormonal contraception among women (Bouma et al, 2009;Kudielka et al, 2007;Kudielka and Kirschbaum, 2005;Liening et al, 2010). Despite controlling for these variables in our study, we still observed considerable variation in the stress response.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…1 A recent review article in Molecular Psychiatry questioned the validity of ATD. 2 Although we agree that ATD's effects on 5-HT activity at the molecular level need further clarification, van Donkelaar et al 2 goes too far in challenging whether ATD exerts its effects through serotonergic mechanisms. There is strong evidence that ATD reduces brain 5-HT and disrupts stimulated 5-HT release, 3,4 and converging translational findings support a central role for brain 5-HT in ATD's effects on cognition and behavior.…”
mentioning
confidence: 83%
“…There is strong evidence that ATD reduces brain 5-HT and disrupts stimulated 5-HT release, 3,4 and converging translational findings support a central role for brain 5-HT in ATD's effects on cognition and behavior. [5][6][7] Van Donkelaar et al 2 does not dispute the fact that ATD reduces 5-HT synthesis and brain 5-HT levels. 4 Their arguments converge on two issues.…”
mentioning
confidence: 99%